قاعدة الضـرورات تبـيح الـمحـظـورات وتـطـبيقها في جـواز كـشف وجه الـمتـنـقـبة: The Principle of al-Ḍārūrāt Tubīḥu al-Maḥẓūrāt and Its Implementation Regarding Permissibility for Women to Unveil Their Face - Mukran Usman; Askar Patahuddin; Andi Muhammad Ihsan Yusuf (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Research presented in front of dear readers talks about the law of using and disclosing the niqab in necessity in implementing the rules of al-dharuratu tubiihul mahzhuraat. Among the objectives are identifying the laws of wearing the niqab, the dhabith of necessity, and the application of the principle of al-dharuratu tubiihul mahzhuraat. Researchers limit the application of the principle to four situations, namely: First, in the making of ID cards, passports, or other things that required photographs. Second, in the medical field and when a disaster strikes. Third, the husband and his family forced the wife to remove the veil. Fourth, what has recently emerged is the coercion of several universities or company directors on students or employees to remove their niqab. The scientific method that the researcher followed in this study to achieve the results of these problems were as follows: descriptive method, inductive method, and deductive method. The results showed: First, the preponderant one concerning wearing the niqab is that it is obligatory based on the strength of this argument, and it is closer to chastity in the time of fitnah spreading and the amount of immorality that is happening today. Second, the basic principle of a woman when she leaves her home or appears to strangers is the obligation to cover her face and the prohibition of opening it, whether she is worried about temptation in herself or against her, or even though she feels safe from temptation, but is allowed to remove it in a necessity because in a necessity, forbidden things are allowed, but it is important to know consideration of a situation so that it is called a necessity by which it can be known to what extent the implementation of the rule regarding the permissibility of showing one's face so that it is not used as an excuse for committing forbidden acts.